Adult education in the Nordic countries - Nordic co-operation in the field of education - Nordic Council; Secretariat for Nordic Cultural Cooperation (Nordic Council, 1976)
The Survey has been translated from the Nordic languages into English by persons appointed by the Nordic Ministries of Education.